Effect of vacuum or modified atmosphere packaging (MAP) in combination with a CO2 emitter on quality parameters of cod loins (Gadus morhua). (September 2016) - Hansen, Anlaug Ådland; Moen, Birgitte; Rødbotten, Marit; Berget, Ingunn; Pettersen, Marit Kvalvåg
Highlights: CO2 emitter prolongs shelf life of traditional vacuum packaged cod loins. CO2 emitter also prolongs shelf life of MAP with low headspace volume. Increasing CO2 levels resulted in improved quality preservation. Use of CO2 emitter increased shelf life by 2–4 days compared to no emitter. Photobacterium sp. was the dominating bacterium for all packaging methods. Abstract: Bacterial growth, microbiota and sensory quality of cod loins (farmed Atlantic cod, Gadus morhua ) was studied during 15 days of storage (2 °C), packaged in vacuum or in modified atmosphere package (MAP, 60% CO2 /40% N2, g/p ratio 1.6/1), with a CO2 emitter pad or a liquid absorbent pad. The objective was to investigate how packaging with CO2 emitter can prolong shelf life in vacuum, and in low headspace MAP. Sensory analysis showed that the initial freshness was better preserved by adding a CO2 emitter in both vacuum and MAP. The MAP had equal antibacterial effect compared to vacuum added CO2 emitter. 16S rDNA sequencing showed that CO2 emitter did not alter the dominant bacterial composition and that Photobacterium sp. dominated all packaging methods. Vacuum packaged samples past shelf life after 7 days of storage, vacuum added a CO2 emitter and MAP after 9 days, and MAP added a CO2 emitter after 13 days.